Management of multiple sclerosis using disease-modifying therapies: a clinical review. (2nd April 2022) - Thomas, Sue; Stross, Ruth
Abstract : Multiple sclerosis is a chronic neurological disease of the central nervous system with an autoimmune inflammatory basis that presents with clinical variability and progressive disability. The most common type of multiple sclerosis presents with a relapsing and remitting pattern. A range of disease-modifying treatments are available to treat multiple sclerosis, with more to come in the drug pipeline. This article briefly summarises multiple sclerosis alongside the range of disease-modifying treatments that are currently available. Two patient scenarios are outlined to illustrate how disease-modifying treatments may be prescribed. The article highlights that efficacy of treatment is not the only consideration for prescribing. The needs of the person with multiple sclerosis and their family must also be considered, alongside social issues, such as participation and employment, the impact the treatment has on the NHS workforce, and the capacity and financial impacts. Therefore, this article highlights the complex nature of the treatment decisions.